ABOUT INTANGIBLE MOTIVATION OF WORKER’S OF THE COMPANIES IN CONDITIONS OF ECONOMIC CRISIS - Данилюк, Микола Олексійович; Волошинюк, Оксана Романівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The article is dedicated to the question of intangible motivation’s efficiency in conditions of economic crisis. The steps for increasing of motivation’s efficiency and using of labor potential are recommended. Basing upon the world experience’s analysis, the main directions and the ways of intangible motivation are distinguished, its role is determined and the meaning for enterprises under conditions of limited money resources and reducing of expenses on staff motivation.